HDN of Indole over Ir-modified Ti-SBA-15 - Ledesma, Brenda Cecilia Soledad (2016)
The hydrodenitrogenation of indole has been studied over a series of Ti-modified SBA-15 supports and their respective Ir-catalysts. Ti-SBA-15 was synthesized using sol-gel method and Ti was added during the synthesis using Tetraethyl Orthotitanate. Iridium was added by wetness impregnation. The acidity of Ti-SBA-15 was modified adding F or Al in order to improve the catalytic activity. The catalysts prepared were extensively characterized by X-ray diffraction (XRD), N2 adsorption isotherms, UV-vis-DRS, Raman spectroscopy, 27Al-MAS-NMR spectroscopy, XPS, TEM-EDS, Py-FTIR, H2-Chemisorption and TPR. UV-vis-DRS and Raman spectroscopy confirmed that Ti was incorporated in tetrahedral coordination in the framework of the SBA-15. The analysis showed that the mesoporous structure was maintained after F or Al incorporation. 27Al-MAS-NMR spectroscopy indicated that aluminum was incorporated mainly in Td positions. The results showed that Ti incorporation helps to reduce significantly the size of iridium crystallites and improves its dispersion considerably. Ir/Ti-SBA-15 modified with Al, with Bronsted acidity, was the most active catalyst for indole HDN, in mild conditions in a Batch reactor. The experimental data for indole hydrodenitrogenation was quantitatively represented by a Langmuir-Hinshelwood type rate equation.